Penerapan Prinsip Kepatuhan Hukum sebagai Upaya Pencegahan Penggelapan Keuangan dalam Korporasi - Ainyes Priskila Sari; Sri Astutik; Vieta Imelda Cornelis; Noenik Soekorini (Jurnal Hukum Lex Generalis, 2025)
Abuse of authority by corporate managers or directors in using their positions to divert company funds for personal or group interests in the form of embezzlement that is not in accordance with corporate objectives and compliance principles. This study aims to analyze the form of financial embezzlement violations by corporations as well as law enforcement and efforts to prevent criminal acts of embezzlement in corporations based on the principle of legal compliance. This study uses a normative legal research method and uses a legislative approach and a conceptual approach. The results obtained from the study are that the form of violation committed is Embezzlement of Funds by Employees or corporate managers directly by taking or using company financial assets without legal knowledge and approval. Law enforcement and prevention efforts carried out are by applying Article 372 of the Criminal Code to be the basis for imposing sanctions on perpetrators of criminal acts of embezzlement. Furthermore, in efforts to prevent criminal acts of embezzlement in corporations, by applying the principles of compliance with company regulations that apply to corporations. Efforts to prevent criminal acts of embezzlement in the corporate realm are also carried out by implementing PERMA Number 13 of 2016, concerning Procedures for Handling Criminal Cases in Corporations, which gives judges the authority to criminalize corporations as legal subjects.